Application of novel nanomaterials with dual functions of antimicrobial and remineralization in mouthwashes - Lin Chang; Ruihuan Gan; Xiaoyu Huang; Dali Zheng; Chen Su; Youguang Lu; Yan Feng (Scientific Reports)
Abstract The study aims to improve the antimicrobial and remineralization-promoting properties of mouthwash by synthesizing novel Ag/ZnO/Oyster Shells nanocomposites and evaluating their anti-caries properties and biosafety in vitro and in vivo, so as to reduce the incidence of caries. The antimicrobial properties of the synthesized Ag/ZnO/Oyster Shell nanocomposites were examined by bacterial inhibition zone, minimum inhibitory concentration, minimum bactericidal concentration, fluorescence staining and scanning electron microscopy. The potential of the materials to promote remineralization of demineralized enamel was detected by scanning electron microscopy, surface microhardness and depth of hard tissue defects, and laser confocal electron microscopy analysis. The synthesized materials were then incorporated into mouthwash, and their effects on antimicrobial properties, remineralization-promoting properties were evaluated. Furthermore, an oral mucosal contact model was established to assess local irritation and systemic effects. The results showed that the novel Ag/ZnO/Oyster Shell nanocomposites possessed strong antimicrobial activity, remineralization-promoting ability and good biosafety, and the mouthwash containing Ag/ZnO/Oyster Shell possessed strong antimicrobial performance and remineralization-promoting ability, and showed no obvious abnormalities in local mucosal tissues, blood indices, and histopathology of the liver and kidneys in the oral exposure model of the SD rats. These findings indicate that Ag/ZnO/Oyster shell incorporated into mouthwash has strong antimicrobial activity, good remineralization-promoting properties and good biosafety in vivo. It is therefore expected to be used in clinical applications.